Green turtle head trauma with intracerebral hemorrhage: image diagnosis and treatment - Goldberg,Daphne Wrobel (2010)
Sea turtles are threatened to the point of extinction. The major goal of rehabilitating injured individuals is to eventually reintroduce them back into their habitat. Sea turtles are vulnerable to anthropogenic effects, and impact traumas are a common cause of death among these animals. Carapace and skull fractures are usually related to vessel collisions or propeller impacts. However, intentional traumas inflicted by humans are also considered as a potential threat. The purpose of this article is to describe the diagnosis and rehabilitation procedures of a juvenile green turtle (Chelonia mydas) after severe head trauma with brain hemorrhage. The data presented here can be used as a reference for future cases of head trauma in chelonians.